Shared decision-making and health for First Nations, Métis and Inuit women: a study protocol - Jull, Janet; Stacey, Dawn; Giles, Audrey; Boyer, Yvonne; Minwaashin Lodge, the Aboriginal Women's Support Centre (BMC Medical Informatics and Decision Making, 2012)
Background Little is known about shared decision-making (SDM) with Métis, First Nations and Inuit women (“Aboriginal women”). SDM is a collaborative process that engages health care professional(s) and the client in making health decisions and is fundamental for informed consent and patient-centred care. The objective of this study is to explore Aboriginal women’s health and social decision-making needs and to engage Aboriginal women in culturally adapting an SDM approach. Methods Using participatory research principles and guided by a postcolonial theoretical lens, the proposed mixed methods research will involve three phases. Phase I is an international systematic review of the effectiveness of interventions for Aboriginal peoples’ health decision-making. Developed following dialogue with key stakeholders, proposed methods are guided by the Cochrane handbook and include a comprehensive search, screening by two independent researchers, and synthesis of findings. Phases II and III will be conducted in collaboration with Minwaashin Lodge and engage an urban Aboriginal community of women in an interpretive descriptive qualitative study. In Phase II, 10 to 13 Aboriginal women will be interviewed to explore their health/social decision-making experiences. The interview guide is based on the Ottawa Decision Support Framework and previous decisional needs assessments, and as appropriate may be adapted to findings from the systematic review. Digitally-recorded interviews will be transcribed verbatim and analyzed inductively to identify participant decision-making approaches and needs when making health/social decisions. In Phase III, there will be cultural adaptation of an SDM facilitation tool, the Ottawa Personal Decision Guide, by two focus groups consisting of five to seven Aboriginal women. The culturally adapted guide will undergo usability testing through individual interviews with five to six women who are about to make a health/social decision. Focus groups and individual interviews will be digitally-recorded, transcribed verbatim, and analyzed inductively to identify the adaptation required and usability of the adapted decision guide. Discussion Findings from this research will produce a culturally sensitive intervention to facilitate SDM within a population of urban Aboriginal women, which can subsequently be evaluated to determine impacts on narrowing health/social decision-making inequities.